Acute toxicity and determination of the active constituents of aqueous extract of uncaria tomentosa bark in hyphessobrycon eques - Yunis Aguinaga, Jefferson [UNESP]; Claudiano, Gustavo S. [UNESP]; Marcusso, Paulo F. [UNESP]; Ikefuti, Cynthia [UNESP]; Ortega, George G.; Eto, Silas F. [UNESP]; da Cruz, Claudinei [UNESP]; Moraes, Juliet R. E. [UNESP]; Moraes, Flávio R. [UNESP]; Fernandes, João B. K. [UNESP] (Hindawi Publishing Corporation, 2014)
Uncaria tomentosa is a medicinal plant used in folk medicine by Amazon tribes. In this study the constituents of aqueous extract of U. tomentosa bark were quantified by chromatographic technique and its lethal concentration 50 (48 h) in Hyphessobrycon eques was determined. The chromatography showed high levels of oxindole alkaloids, quinovic acid glycosides, and low molecular weight polyphenols. The CL50 48 h was 1816 mg/L. Fish showed behavior changes at concentrations above 2000 mg/L, accompanied by a significant decrease of dissolved oxygen. At the highest concentration 100% mortality was observed attributed to oxygen reduction by the amount of oxindole alkaloids, polyphenols accumulation of the extract in the gills, and the interaction of these compounds with dopamine. In conclusion, the aqueous extract of U. tomentosa did not alter the chemical components and it was shown that U. tomentosa has low toxicity to H. eques; therefore, it can be used safely in this species.